Problem teaching technology. types of teaching - Yakubova Nafisa Odiljanovna; Yusupova Shohista Alimjanovna; Nusharov Bobir Bolbekovich (International Journal on Orange Technologies, 2021)
The purpose of engineering graphics for the formation of the child's worldview, the formation of spatial imagination, as well as modeling and construction through drawing lessons is stated